2018
DOI: 10.3174/ajnr.a5639
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Apparent Diffusion Coefficient for Assessment of Tumor Progression in Patients with Low-Grade Glioma

Abstract: BACKGROUND AND PURPOSE:Early and accurate identification of tumor progression in patients with low-grade gliomas is challenging. We aimed to assess the role of quantitative ADC analysis in the sequential follow-up of patients with low-grade gliomas as a potential imaging marker of tumor stability or progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…PET-scan and diffusion MRI have previously been used to predict MP in LGG. In one study, the interval change of the 10th percentile ADC predicted progression on average 8 months before the RANO criteria in 12 of 13 patients with progressive LGG compared to 3 of 15 with stable disease [ 16 ]. In another study, MP appeared after 2 to 27 months after initial diagnosis in 78% of diffuse LGG with 18 F-FET-PET uptake shortly after the diagnosis compared to 0% with circumscribed LGG without uptake [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…PET-scan and diffusion MRI have previously been used to predict MP in LGG. In one study, the interval change of the 10th percentile ADC predicted progression on average 8 months before the RANO criteria in 12 of 13 patients with progressive LGG compared to 3 of 15 with stable disease [ 16 ]. In another study, MP appeared after 2 to 27 months after initial diagnosis in 78% of diffuse LGG with 18 F-FET-PET uptake shortly after the diagnosis compared to 0% with circumscribed LGG without uptake [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic accuracy regarding PTZ was not scrutinized, possibly because of the scarce literature focusing on this specific subject. Interestingly, a study on tumor proliferation that focused exclusively on DLGG found that the interval changes of ADC values correctly predicted disease progression (diagnostic accuracy of 86%) before apparent radiologic progression on conventional imaging [43], supporting the potential use of radiomics in detecting peritumoral cells.…”
Section: Flair Mri Cannot Reflect the Ptz: How Can Dlgg Delineation B...mentioning
confidence: 95%
“…Multiparametric evaluations have shown that a change in only 1 or 2 MRI features of a low-grade glioma, for example, focal low ADC, high relative cerebral blood volume, or a change in metabolic profile on proton magnetic resonance spectroscopy ( 1 H magnetic resonance spectroscopy), can suggest early high-grade transformation before any observable contrast enhancement on conventional MRI. 30,31 Such knowledge may be considerably beneficial for management of IDH-mutated tumors, because their distinct metabolism presents a feasible target for novel therapeutic agents. 32 Taking into consideration that glioblastomas only very rarely display a T2-FLAIR mismatch sign, we speculate that in some patients with mismatch-positive, residual or recurrent lower-grade gliomas, an early shift toward a grade IV lesion may be detected by observing a morphological and/or quantitative change in diffusivity from the initial mismatch pattern, possibly even preceding a discernible change on conventional T2W and FLAIR images.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, gliomas bearing a T2-FLAIR (or T2-DWI) mismatch sign revealed significantly higher mean ADC values, confirming an earlier finding by Foltyn et al 10 and suggesting that a separate range of ADC values may be required to form an adequate quantitative baseline for follow-up purposes in this tumor subset. Multiparametric evaluations have shown that a change in only 1 or 2 MRI features of a low-grade glioma, for example, focal low ADC, high relative cerebral blood volume, or a change in metabolic profile on proton magnetic resonance spectroscopy ( 1 H magnetic resonance spectroscopy), can suggest early high-grade transformation before any observable contrast enhancement on conventional MRI 30,31 . Such knowledge may be considerably beneficial for management of IDH -mutated tumors, because their distinct metabolism presents a feasible target for novel therapeutic agents 32 .…”
Section: Discussionmentioning
confidence: 99%